Environmental analysis - Kleibohmer, Wolfgang (New York : Elsevier, 2001)
"Environmental Analysis" covers a compilation of analytical methods for the determination of a wide range of environmental priority pollutants, including amines, polycyclic aromatic hydrocarbons, pesticides, phenols, PCBs, and also including organometallic species, polycyclic aromatic sulphur heterocycles and metabolites of polycyclic aromatic hydrocarbons. For all environmental pollutants, an overview and an assessment of value of a broad range of relevant methods including conventional techniques but also of advanced separation and sample preparation techniques given, with all possible matrices being considered. This book does not only give up-to-date material on sampling and sample pre-treatment, extraction techniques, clean-up, pre-fractionation, different types of chromatographic methods and quality assurance, but also information on actual and upcoming analytical problems, such as the determination of polycyclic aromatic sulphur heterocycles and of metabolites of PAH. The final chapter is devoted to the important role of analytic separation methods in water quality control. Experienced and well-known authors have contributed their knowledge and expertise to individual chapters.
Gas chromatographic analysis of environmental amines with selective detectors / Hiroyuki Kataoka, Shigeo Yamamoto and Shizuo Narimatsu -- Modern techniques for the analysis of polycyclic aromatic hydrocarbons / Hian Kee Lee -- Separation methods in the analysis of polycyclic aromatic sulfur heterocycles / Jan T. Andersson -- Polycyclic aromatic hydrocarbon (PAH) metabolites / A. H{uml}oner -- Pesticides defined by matrix / John R. Dean and Lisa J. Fitzpatrick -- Phenols / Olga J{acute}auregui and M. Teresa Galceran -- Polychlorinated biphenyls / Jacob de Boer -- Metal species / Rolf-Dieter Wilken -- Water quality / C. Zwiener and F.H. Frimmel.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Environmental chemistry -- Methodology; Chemistry, Analytic -- Methodology; Pollutants -- Analysis; Electronic books